Proteome-wide analysis of hydrogen peroxide-induced protein carbonylation in Arabidopsis thaliana - Fangue-Yapseu, Georges Yannick; Tola, Adesola Julius; Missihoun, Tagnon D. (Frontiers in Plant Science, 2022)
Protein carbonylation is a non-enzymatic and irreversible post-translational modification that occurs naturally in living organisms under the direct or indirect effect of reactive oxygen species (ROS). In animals, signaling pathways involving numerous carbonylated proteins have been identified, highlighting the dual role of these molecules in ROS signal transduction. In plants, however, studies on phytohormone signaling (auxin, methyl jasmonate, abscisic acid) have shown that reactive carbonyl species (RCS: acrolein, malondialdehyde, 4-hydroxynonenal, etc.), derived from the action of ROS on lipids, play important roles in secondary root formation and stomatal closure. However, the carbonylated proteins involved in these signaling pathways remain to be identified. In this study, we analyzed proteins responsive to carbonylation by exogenous hydrogen peroxide (H2O2) by profiling the carbonyl proteome extracted from Arabidopsis thaliana leaves after H2O2 treatment. Carbonylated proteins were enriched at the peptide level and analyzed by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). We identified 35 and 39 uniquely carbonylated proteins in the untreated and the H2O2-treated plant samples, respectively. In comparison to the control treatment, gene ontology analysis revealed that most of the carbonylated proteins identified in the H2O2-treated plant samples are related to sulfate adenylyl transferases and amidophosphoribosyl transferases involved in the immune system response, defense response, and external stimulus-response. These results indicated that exogenous H2O2 caused a change in the pattern of protein carbonylation in A. thaliana leaves. Protein carbonylation may thus influence the plant transcriptome and metabolism in response to H2O2 and ROS-triggering external stimuli.